Working together with people with intellectual disability to make a difference: a protocol for a mixed-method co-production study to address inequities in cervical screening participation - Bateson, Deborah; Ussher, Jane; Strnadová, Iva; Loblinzk, Julie; David, Michael; Chang, Ee-Lin; Carter, Allison; Sweeney, Sally; Winkler, Lauren; Power, Rosalie; Basckin, Caroline; Kennedy, Elizabeth; et al. (Frontiers in Public Health, 2024)
Introduction Cervical cancer is one of the most preventable cancers yet remains a disease of inequity for people with intellectual disability, in part due to low screening rates. The ScreenEQUAL project will use an integrated knowledge translation (iKT) model to co-produce and evaluate accessible cervical screening resources with and for this group. Methods Stage 1 will qualitatively explore facilitators and barriers to screening participation for people with intellectual disability, families and support people, healthcare providers and disability sector stakeholders (n≈20 in each group). An accessible multimodal screening resource, accompanying supporting materials for families and support people, and trauma-informed healthcare provider training materials will then be co-produced through a series of workshops. Stage 2 will recruit people with intellectual disability aged 24 to 74 who are due or overdue for screening into a single-arm trial (n=48). Trained support people will provide them with the co-produced resource in accessible workshops (intervention) and support them in completing pre-post questions to assess informed decision-making. A subset will participate in qualitative post-intervention interviews including optional body-mapping (n≈20). Screening uptake in the 9-months following the intervention will be measured through data linkage. Family members and support people (n=48) and healthcare providers (n=433) will be recruited into single arm sub-studies. Over a 4-month period they will, respectively, receive the accompanying supporting materials, and the trauma-informed training materials. Both groups will complete pre-post online surveys. A subset of each group (n≈20) will be invited to participate in post-intervention semi-structured interviews. Outcomes and Analysis Our primary outcome is a change in informed decision-making by people with intellectual disability across the domains of knowledge, attitudes, and screening intention. Secondary outcomes include: i) uptake of screening in the 9-months following the intervention workshops, iii) changes in knowledge, attitudes and self-efficacy of family members and support people, iii) changes in knowledge, attitudes and preparedness of screening providers. Each participant group will evaluate acceptability, feasibility and usability of the resources. Discussion If found to be effective and acceptable, the co-produced cervical screening resources and training materials will be made freely available through the ScreenEQUAL website to support national, and potentially international, scale-up.